Foreign banks and financial stability in emerging markets: Evidence from the global financial crisis - Ursula Vogel; Adalbert Winkler (Frankfurt School of Finance & Management, 2010)
Foreign banks have increased their market share in many emerging markets since the mid-1990s. We examine whether this contributed to financial stability in the respective host countries in the global financial crisis. Our results suggest that the stabilizing impact of foreign banks was limited to the cross-border component of financial globalization and to two regions: Eastern Europe and Sub-Saharan Africa. Only in the latter region was this translated into more stable credit growth. Thus hopes that a stronger presence of foreign banks might help host countries in isolating domestic credit from international shocks did not materialize in the current crisis.
Keywords: E44; F36; G21; 330; Foreign banks; cross-border lending; bank credit; financial crisis; Internationale Bank; Kreditgeschäft; Finanzmarktkrise; Spillover-Effekt; Aufstrebende Märkte; Schwellenländer